Teaching geometry in school: Digital resources to develop students’ spatial thinking - Abylkassymova, Alma; Yessetov, Yelzhan; Tuyakov, Yessenkeldy; Ardabayeva, Almagul (International Journal of Innovative Research and Scientific Studies, 2025)
Good school geometry education not only develops logical thinking but also the spatial imagination and thinking of students. The main means of developing spatial thinking is solving stereometric problems and especially making drawings for these problems. In current practice, teaching students how to construct images of geometric shapes is a challenging task. Weaknesses in geometric preparation are manifested primarily in the inability to accurately depict geometric figures, perform additional constructions and analyze the constructed drawing. Therefore, creating precise and correct drawings, fostering a culture of working with visual effects and developing spatial thinking skills are all vital skills to teach students in geometry courses. In this regard, digital resources and specialized mathematics programs serve as powerful learning tools. The purpose of this study is to identify the significance of digital resources in solving geometric problems for the development of students’ spatial thinking. This paper discusses the relationship between the type of spatial thinking and geometric problems for reasoning and digital technologies, presents digital educational materials and resources and provides recommendations for their integration into the educational program. The research methods of this study include observation, study and generalization of teaching experience, interviewing, surveying and testing students, development of methodology and digital resources. A pedagogical experiment was conducted to test the effectiveness of the developed methodology. The results showed the effectiveness of digital resources in the learning process with a noticeable improvement in students’ spatial thinking skills observed due to the introduction of digital education.